Eclectic approach as idea of e-educounseling preliminary system model - Jumail, Jumail; Noordin, Mohamad Fauzan; Muhamad Ibrahim, Najhan; R., Mujastuti; R. D., Risanty (IOP Publishing, 2021)
Counseling is a dynamic and purposeful relationship between counselor and counselee. Directive approach was a counseling approach that concerned on the powerful experience of the counselor, which is he/she can direct the student to solve problem accordingly. Non-directive approach was a counseling approach that concern on the student centered counseling, which is allow the student to independency solve their own problem by counselor motivation and encouragement. Eclectic approach is introduced as one of the approaches which are integrated both directive and non-directive to be powerful balance educational counseling approach. In this study the superiority and experience of the counselor and independency of the student are considered as a balance key of counseling process. Furthermore, some weaknesses on the most of current e-counseling system model was focused on the users, however they forgot that each counseling approach has it unique process that can be considered. Therefore, this study try to integrate two different approach directive and non-directive become one known approach called eclectic approach. As the objective of the study an e-educounseling system model based eclectic approach are designed. The e-educounseling system model is focused on the real eclectic counseling process and not only focused on the functional requirements.